Effect of tin addition on the corrosion resistance of low‐alloyed steel in simulated coastal‐industrial atmosphere environment. Issue 10 (5th October 2022) - Chen, S.; He, M.; Liu, B.
Abstract: In simulated coastal‐industrial atmosphere, the atmospheric corrosion behavior of three different tin content low‐alloy steels has been investigated by indoor wet/dry cyclic corrosion test. The results indicate that in the early stage of atmospheric corrosion, tin addition has beneficial effect on the corrosion resistance improvement, and corrosion resistance increases as tin content increases. However, increased corrosion resistance due to tin addition does not last long. After a large amount of corrosion products are formed on the surface of the sample, the stability and compactness of rust layer are degraded by tin. Therefore, in the long‐term atmospheric corrosion process, the lower the tin content in steel, the better the corrosion resistance of steel. Abstract : The atmospheric corrosion behavior of three different tin content low‐alloy steels has been investigated. In the early stage of atmospheric corrosion, tin addition is beneficial, but does not last long. In the long‐term atmospheric corrosion process, the lower the tin content in steel, the better the corrosion resistance of steel.